Correspondence between plaque index and Streptococcus mutans and Lactabacillus spp. counts in a child population: A cross-sectional study - Arango, María Cristina; González, Pamela; Perea, Alejandra; Villegas, Lina María; Martínez Cajas, Carlos Humberto; Villavicencio, Judy (Revista Estomatología, 2020)
Background: The identification of microorganisms such as Streptococcus mutans (SM) and Lactobacillus spp. (LB) is a predictor of the development of caries, however the identification methods are of limited access due to their high cost. Aim: the objective of this study was to determine the correlation between the dental biofilm measured by the modified Silness and Löe dental plaque index (DPI)) and the SM and LB count, in preschool children from Colombia. Materials and methods: This is a descriptive cross-sectional and correlational study. We took 202 samples from children between 3 and 4 years of age from three kindergartens in Cali, Colombia, belonging to socioeconomic stratum 1 and 2, evaluated at four times (0, 3, 6 and 9 months). Results: We found a correlation between the highest IPB and the highest count of SM colony forming units only at 3 months (p = 0.003*). LB counts were homogeneous in all children and there was no correlation with IPB. Conclusion: We observed mixed results on the relationship between IPB and the counts of SM present in the saliva, therefore an analysis of multiple factors is required.